Woman and Cyberbullying - Kartika Sulastri (STMIK Pontianak, 2020)
The seminar titled ‘Woman and Cyberbullying’ as part of Social Community Services has been conducted in Vocational School Number Five (SMKN 5) Pontianak, West Kalimantan. This aimed at raising awareness yet broadening the horizons of high school students about cyberbullying, the drawbacks, and the consequences. The focus of this seminar is on adolescents who not only are vulnerable to cyberbullying but also potentially to be the perpetrators. A comprehensive understanding regarding various kinds of intimidations is expected to develop healthy mental awareness of adolescents. An intense persuasive approach to teenagers -particularly high school students- is needed, so that, they can consciously recognize various types of cyberbullying and be able to prevent and to deal with them necessarily, then become physically and mentally confident mothers in the future. The assessment of students’ understanding of 33 participants about cyberbullying using questionnaires showed an escalation, where students can understand they can be the victims as well as the perpetrators. They obtained oral statements in class to refrain from unnecessary comments and set a wiser social behavior to prevent cyberbullying incidents.